Prognostic Factors for Hearing Recovery Following Sudden Sensorineural Hearing Loss in Singapore: A Multivariate Analysis - Nazimah Syarif; Vita Amanda; Shina Abdulkadir (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Sudden sensorineural hearing loss (SSNHL) is an otologic emergency characterized by an unexplained, rapid loss of hearing, usually in one ear. Identifying prognostic factors for hearing recovery is crucial for guiding treatment strategies and patient counseling. This study aimed to determine the prognostic factors associated with hearing recovery in a cohort of SSNHL patients in Singapore. Methods: A retrospective cohort study was conducted involving 150 patients diagnosed with SSNHL at three tertiary referral hospitals in Singapore between January 2019 and December 2022. Data on demographics, clinical characteristics (degree and configuration of hearing loss, presence of vertigo and tinnitus), treatment modalities (corticosteroids, hyperbaric oxygen therapy), and hearing outcomes at 1, 3, and 6 months following diagnosis were collected. Hearing recovery was defined as an improvement of at least 15 dB in pure-tone average (PTA) across frequencies 0.5, 1, 2, and 4 kHz. Multivariate logistic regression analysis was performed to identify independent predictors of hearing recovery. Results: The mean age of the participants was 47.5 ± 12.8 years. Complete hearing recovery was observed in 48% of patients at 6 months. Multivariate analysis revealed that younger age (OR = 0.95, 95% CI: 0.92-0.98, p=0.003), absence of vertigo (OR = 3.15, 95% CI: 1.52-6.53, p=0.002), and prompt initiation of corticosteroid therapy (OR = 2.87, 95% CI: 1.38-5.97, p=0.005) were independent predictors of favorable hearing recovery. The degree of initial hearing loss and the presence of tinnitus were not significantly associated with hearing outcomes. Conclusion: Younger age, absence of vertigo, and early initiation of corticosteroid therapy are associated with better hearing outcomes in Singapore patients with SSNHL. These findings underscore the importance of prompt diagnosis and treatment to maximize the chances of hearing recovery.